Taxonomic revision of the genus Wurdastom (Melastomataceae, Cyphostyleae) - Mendoza Cifuentes, Humberto (Instituto de Ecología, A.C., 2020)
Background and Aims: Wurdastom is a little-known neotropical genus, which is poorly represented in herbarium collections. A historical summary,discussion about the tribal position, taxonomic review, and a conservation assessment of each species of the genus was carried out.Methods: Wurdastom specimens of 17 herbarium collections from Colombia (CAUP, COAH, COL, CUVC, FMB, HUQ, PSO, UDBC, UPTC, VALLE), Ecuador (QCA, QCNE), and the United States of America (CAS, F, MO, NY, US) were reviewed, and relevant type collections available at JSTOR Global Plants were consulted. An identification key, descriptions, illustrations and distribution maps for each species were developed. IUCN guidelines and criterio were used for conservation assessments of each species.Key results: In total, 52 Wurdastom collections were found in the revised herbaria. A new species from Colombia is described and new isotypes from the VALLE Herbarium are reported here for the first time. Wurdastom is a small genus of trees and shrubs from central-west Colombia to northern Peru where it grows in Andean and humid lowland tropical forests. The genus, which is assigned to the tribe Cyphostyleae, is characterized by the acrodromous venation, barbellate trichomes on vegetative parts and inflorescences, multiflorous thyrsoid or pleiothyrsoid inflorescence, haplostemonousflowers, petals ≤1 cm long, inferior ovaries, and capsular fruits.Conclusions: Wurdastom includes eight neotropical species, most of them with restricted distributions. One species is assessed here as Threatened (W. sneidernii), two as Vulnerable (W. cuatrecasasii, W. dudleyi), and the rest are treated as Data Deficient.